TRANSCULTURAL COMMUNICATION: THE INTERNATIONAL STU-DENTS’ STRATEGIES FOR BULDING SOCIAL INTERACTION WITH LOCAL STUDENTS AT UNIVERSITAS MUHAMMADIYAH MAKAS-SAR - Nurilmi Aulia Amar; Nurdevi Bte Abdul; Herlina Daddi (English Study Program University of Pasir Pengaraian, 2026)
The increasing number of international students has created multicultural interaction in higher education environments. However, in the context of higher education in Indonesia, language differences, local accents, and the use of regional expressions often pose challenges for international students. Previous research has focused more on language barriers and cultural adaptation, while studies on transcultural communication and the use of artificial intelligence (AI) as a communication tool are still limited, especially in Indonesian multicultural higher education contexts. Therefore, this study investigates transcultural communication strategies and communication challenges experienced by Thai students at Universitas Muhammadiyah Makassar. This study employed a qualitative ethnographic approach involving three Thai university students from different study programs who were purposively selected due to their active engagement in multicultural academic interactions and their varying levels of Indonesian language proficiency.Data were collected through interviews, observations, and field notes, then analyzed using thematic analysis. The results showed that participants employed strategies such as asking for clarification, mixing languages, using peer assistance, gestures, and repeated interactions to maintain communication. Furthermore, the study identified the use of AI as a novel strategy for understanding contextual meaning and cultural expressions during interactions. Overall, the findings indicate that transcultural communication was facilitated through processes of adaptation, negotiation of meaning, social support, and the use of digital technology